Adaptive FLC-based Shunt Active Power Filter with a PV-Fed DC Link for Improved Current Compensation and THD Mitigation - Budi, SH Suresh Kumar; Kiranmayi, R. (Buletin Ilmiah Sarjana Teknik Elektro, 2025)
Power quality improvement with traditional controllers (PI, PID, fixed-parameter FLC) is difficult when dealing with nonlinear, time-varying loads and dynamic grid conditions. For microgrids that incorporate renewable energy sources, it is challenging to acquire the precise mathematical models that are necessary for this work. To address power quality challenges, such as distortion of current and Total Harmonic Distortion (THD), produced by nonlinear loads in PV fed systems, such as solar energy conversion, this publication proposes an Adaptive Fuzzy Logic Controller (FLC) based shunt Active Power Filter (APF). An analysis of the power quality enhancement achieved in a distribution power system using a single-stage solar PV integrated shunt APF is presented in this paper. In order to improve load side parameters, such as the elimination of even and odd current harmonics utilizing shunt APF is employed. This filter makes use of a shared DC-link voltage source. In addition, it transfers energy from the PV system's solar panels to the DC link voltage, which is an extra effort. In this paper, It looks at a single-phase inverter that uses an Adaptive FLC to improve parameters on the source and load sides, as well as harmonics, in grid-connected Distributed Generation systems. Also included is a detailed description of the active power filter's chosen current reference generator. Results that have been validated are attained using MATLAB/SIMULINK(R2023b).